ANALISIS PENGGUNAAN OBAT ANTI TUBERKULOSIS PADA PASIEN TUBERKULOSIS PARU KASUS BARU RAWAT JALAN DI RUMAH SAKIT ATMA JAYA - Yelfi Anwar; Fitri Ayuni (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
ABSTRACT Tuberculosis (TB) is a contagious infectious disease caused by Mycobacterium tuberculosis. The prevalence of pulmonary tuberculosis incident was included in the top 10 highest disease at Atma Jaya Hospital. Therefore, the study of the analysis of the use of anti-tuberculosis drugs in patients with new cases of lung rational at Atma Jaya Hospital indispensable. The purpose of this study was to determine the profile and analyze the rationality of the use of anti-tuberculosis drugs used in outpatients suffering from pulmonary tuberculosis new cases over the period July 2013 - June 2014.